The rule of law in action in democratic Athens - Harris, Edward 1951- (Oxford Univ. Press, 2014)
The author aims to show how the Athenians attempted to put the ideal of the rule of law into action and to understand the nature of litigation in its democratic context. Recent books about the Athenian courts have focused mainly on Athenian social values, but they have paid less attention to the political ideal of the rule of law and to the procedures the Athenians followed to implement this ideal. This study moves beyond the study of rhetoric and ideology to examine how the law worked in action, both in the community as a whole and in the courts